Cytotoxicity of benzophenone-3, an organic ultraviolet filter, caused by increased intracellular Zn2+ levels in rat thymocytes. (25th January 2019) - Utsunomiya, Hidekazu; Hiraishi, Riko; Kishimoto, Koji; Hamada, Sari; Abe, Shin; Bekki, Yusuke; Kamemura, Norio
Abstract: Benzophenone-3 (BP-3) is often used as an ultraviolet (UV) light filter in sunscreen products. Although BP-3 protects the human skin and hair from damage caused by excessive UV radiation, it is reported to exhibit toxic effects in human. However, the cytotoxicity of BP-3 on various cells is still not well understood. In the present study, the cytotoxicity of BP-3 against rat thymocytes was evaluated using a flow cytometric technique with fluorescent probes. Cell mortality increased significantly after 3 h of exposure to 300 μM BP-3, whereas the mean intensity of 5-chloromethylfluorescein diacetate (5-CMF) fluorescence and cellular content of non-protein thiols decreased significantly. However, the membrane potential of thymocytes was not change by BP-3 treatment. Moreover, intracellular Zn 2+ levels increased significantly in a concentration-dependent manner in response to 30 μM BP-3 or higher. The BP-3-induced changes in intracellular Zn 2+ levels and non-protein thiol content increased the vulnerability of thymocytes to oxidative stress. We concluded that BP-3-induced cytotoxicity may be caused by oxidative stress associated with an increase in intracellular Zn 2+ levels. Highlights: Cytotoxicity of BP-3, a UV light filter used in sunscreens products, was evaluated. BP-3-treated rat thymocytes were tested by flow cytometry with fluorescent probes. BP-3 cytotoxicity was caused by Zn 2+ -induced sensitivity to oxidative stress. Results support concerns on BP-3 toxicity and safer agents should be developed.